THE IMPLEMENTATION OF ENTRA (ENGLISH FOR TRANSPORTATION) IN ESP PROGRAM OF PPI MADIUN - Ima Widiyanah; Maya Rizki Amalyasari (Journey: Journal of English Language and Pedagogy, 2019)
The aim of this research is to describe the students' responses on the implementation of EnTra (English for Transportation) in ESP Program of PPI (Politeknik Perkeretaapian Indoneisa) Madiun. The design of this study is descriptive qualitative in which data sources obtained from the students' responses on the interviews and questionnaires after experiencing of using the EnTra Application in English class. The result shows that, from over 60 students as respondents, agree that the application is useful for them in studying English in the area of transportation. There are seven indicators used to measure the student' perception toward the application, those are: aspects of the material relevance, aspects of material organizing, aspects of evaluation / practice questions, aspects of language, aspects of the effects for learning strategies, aspects of software engineering, and aspects of visual appearance. The average students' scoring upon the application after using it for three months is 4,03 based on range scoring 1-5. From this result, it can be concluded that EnTra application is worthy enough to use as the supplementary media in learning English transportation.